Preparation method of lithium-aluminum hydrotalcite and modified diaphragm thereof and in-situ solid-state lithium battery prepared by optimizing electrolyte ratio
Li-aluminum hydrotalcite is prepared by using the co-hydrothermal reaction method in lithium batteries, and combined with optimized electrolyte ratio and in-situ polymerization technology, the shortcomings in lithium batteries in terms of safety and performance are solved, and the electrochemical performance is improved and the safety performance is enhanced.
Patent Information
- Application Number
- CN202411896020.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
Existing lithium metal batteries have safety and performance problems in terms of low flash point of electrolyte solvents and unstable interfaces of electrodes and electrolytes, and the solid electrolyte prepared in situ has shortcomings in compatibility with lithium metal and electrochemical windows.
Li-aluminum hydrotalcite is prepared by co-hydrothermal reaction method and hydrothermal method, and modified separators and solid electrolytes are prepared by optimizing electrolyte ratio and in-situ polymerization technology to improve electrochemical windows and compatibility.
It has achieved improved safety performance and excellent electrochemical performance of lithium batteries, solving the shortcomings in safety and performance of lithium batteries.
Smart Images

Figure CN119706904A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and specifically relates to a method for preparing a lithium aluminum hydrotalcite and a modified diaphragm thereof, and an in-situ solid-state lithium battery prepared by optimizing the electrolyte ratio. Background Art
[0002] Lithium batteries are widely used in mobile phones, computers, drones, aerospace, and new energy vehicles due to their advantages of no memory effect, low self-discharge rate, long cycle life, and low environmental pollution. However, the development of lithium metal batteries (LMBs) also faces huge challenges. On the one hand, the flash point of the electrolyte solvent is low and it is easy to leak, which can lead to combustion and explosion; on the other hand, the interface between the electrode and the electrolyte is unstable, which can easily produce lithium dendrites, triggering side reactions that damage battery performance, and causing short circuits when the dendrites pierce the diaphragm.
[0003] Based on this, researchers have developed polymer-based solid electrolytes (PSEs) materials to solve the above problems. There are two main ways to prepare solid electrolytes: ex-situ preparation and in-situ preparation. Ex-situ prepared solid electrolytes exhibit excellent safety and stability, but they cannot completely penetrate into the pores of the electrode material, resulting in poor interface contact and high interface impedance. In-situ preparation can achieve close contact and good stability at the electrode / electrolyte interface, can provide a connection channel for the rapid transmission of ions, and in-situ polymerization is compatible with the existing battery production system, realizing the simultaneous manufacture of solid electrolytes and battery assembly. The prepared solid electrolyte can better adapt to the volume changes of electrode materials during the charging and discharging process, thereby reducing interface separation caused by volume expansion or contraction.
[0004] However, the solid electrolyte prepared in situ also has some problems, such as poor compatibility with lithium metal and low electrochemical window. Taking into account factors such as cost and compatibility, researchers added functional additives to the electrolyte to improve the compatibility of the electrolyte with lithium metal; introduced inorganic materials to prepare organic-inorganic composite solid electrolytes, which can well balance Li + The commonly used inorganic fillers have excellent transmission capacity, mechanical strength and thermal stability, but there are problems in the preparation process and size control of common inorganic fillers, such as high temperature and high pressure reaction environment, complex process flow, and high requirements for experimental conditions. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a lithium aluminum hydrotalcite and a modified diaphragm thereof and to optimize the electrolyte ratio to prepare an in-situ solid-state lithium battery. The lithium aluminum hydrotalcite provided by the present invention has simple synthesis conditions and is easy to control in size. After the electrolyte formula is optimized, the electrochemical window of the solid electrolyte is significantly improved, the compatibility with lithium metal is good, and at the same time, the solid-state lithium battery has excellent electrochemical performance.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing lithium aluminum hydrotalcite, comprising the following steps:
[0008] A lithium salt, an aluminum salt and water are mixed to obtain a mixed salt solution, NaAlO2, NaOH and water are mixed to obtain an alkaline solution, the alkaline solution is added dropwise to the mixed salt solution to obtain a mixed solution, the mixed solution is subjected to a hydrothermal reaction and then dried to obtain the lithium aluminum hydrotalcite; the temperature of the hydrothermal reaction is 100 to 140°C.
[0009] Preferably, the dropping is carried out in a protective atmosphere, the dropping is carried out under stirring conditions, the dropping temperature is room temperature, the dropping is drop-by-drop, and the dropping is stopped when the pH value of the mixed solution is 12.9-13.
[0010] Preferably, the heat preservation reaction time of the hydrothermal reaction is 8 to 16 hours.
[0011] The present invention also provides a lithium aluminum hydrotalcite obtained by the preparation method described in the above scheme, wherein the interlayer spacing is The interlayer anion is aluminate.
[0012] Preferably, the size of the lithium aluminum hydrotalcite is 300-800 nm.
[0013] The present invention also provides a modified diaphragm, comprising a diaphragm substrate and lithium aluminum hydrotalcite covering both sides of the diaphragm substrate; the lithium aluminum hydrotalcite is the lithium aluminum hydrotalcite described in the above scheme.
[0014] Preferably, the thickness ratio of the diaphragm substrate and the single-sided lithium aluminum hydrotalcite is 3 to 6:1.
[0015] The present invention also provides a method for preparing the modified diaphragm described in the above scheme, comprising the following steps:
[0016] The lithium aluminum hydrotalcite and the binder are mixed to obtain a slurry, and the slurry is coated on both sides of the diaphragm substrate and then dried to obtain the modified diaphragm.
[0017] The present invention also provides a lithium battery, comprising a diaphragm and an in-situ prepared solid electrolyte; the diaphragm is the modified diaphragm described in the above scheme or the modified diaphragm obtained by the preparation method described in the above scheme; the chemical composition of the in-situ prepared solid electrolyte includes ethoxypentafluorocyclotriphosphazene.
[0018] The present invention also provides a method for preparing the lithium battery described in the above scheme, comprising the following steps:
[0019] An in-situ polymerization precursor solution is dripped on both sides of the diaphragm, and a polymerization reaction is carried out after assembly using a liquid battery assembly method to obtain the lithium battery; the diaphragm is the modified diaphragm described in the above scheme or the modified diaphragm obtained by the preparation method described in the above scheme; the chemical components of the in-situ polymerization precursor solution include polymerization monomers, lithium salts, ethoxypentafluorocyclotriphosphazene, initiators and solvents.
[0020] The present invention provides a method for preparing lithium aluminum hydrotalcite. The present invention adopts a co-hydrothermal reaction method and a hydrothermal method, the synthesis conditions are simple, the lithium aluminum hydrotalcite is prepared under water phase conditions, the size of the lithium aluminum hydrotalcite can be adjusted by adjusting the temperature and time of the hydrothermal reaction, the steps are simple, and the operation is convenient.
[0021] The present invention also provides lithium aluminum hydrotalcite obtained by the preparation method described in the above scheme. The lithium aluminum hydrotalcite provided by the present invention has easy size control, is stable at room temperature, has a large interlayer spacing, and has high ionic conductivity.
[0022] The present invention also provides a modified diaphragm. The inorganic component of the modified diaphragm provided by the present invention adopts the lithium aluminum hydrotalcite provided by the present invention, which helps to improve its ion conductivity and has excellent electrochemical performance.
[0023] The present invention also provides a method for preparing the modified diaphragm described in the above scheme. The preparation method provided by the present invention has simple steps, convenient operation, and is easy to achieve large-scale application.
[0024] The present invention also provides a lithium battery. The lithium battery provided by the present invention adopts the modified diaphragm provided by the present invention, combined with ethoxy pentafluorocyclotriphosphazene and in-situ polymerization technology, ethoxy pentafluorocyclotriphosphazene can form Li3N and LiF layers on the surface of the electrode / electrolyte, improve the compatibility with metallic lithium, and ethoxy pentafluorocyclotriphosphazene has the ability to reduce the oxygen concentration around the substance after combustion, and capture the free radicals generated during the combustion and decomposition process, inhibiting the chain reaction of the substance combustion, and combining it with the solid electrolyte greatly improves the safety performance of the battery; in addition, halogen atoms such as fluorine can increase the electrochemical window of the material and improve the electrical performance of the battery.
[0025] The present invention also provides a method for preparing the lithium battery of the above scheme. The preparation method provided by the present invention has low cost, good safety and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 XRD spectrum of lithium aluminum hydrotalcite prepared in Example 1;
[0028] Figure 2 The infrared spectrum of the lithium aluminum hydrotalcite prepared in Example 1;
[0029] Figure 3 The scanning electron microscope images of the lithium aluminum hydrotalcite prepared in Example 1 (a), Example 4 (b) and Example 5 (c);
[0030] Figure 4 The figure is a comparison of the cycle performance of the lithium batteries prepared in Example 1 and Comparative Example 1;
[0031] Figure 5 A comparison chart of the multiple rate performance of lithium batteries prepared in Example 1 and Comparative Example 1;
[0032] Figure 6 This is the LSV test diagram of the lithium battery prepared in Example 1;
[0033] Figure 7 EIS test graphs of lithium batteries prepared in Example 1 and Comparative Example 1;
[0034] Figure 8 This is a comparison chart of the long cycle performance of the lithium batteries prepared in Example 1 and Comparative Example 2;
[0035] Fig. 9 This is a test diagram of the multiple rate performance of lithium batteries prepared in Example 1 and Comparative Example 2;
[0036] Fig.10 These are the EIS test graphs of the lithium batteries prepared in Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0037] The present invention provides a method for preparing lithium aluminum hydrotalcite, comprising the following steps:
[0038] Lithium salt, aluminum salt and water are mixed to obtain a mixed salt solution, NaAlO2, NaOH and water are mixed to obtain an alkaline solution, the alkaline solution is added dropwise to the mixed salt solution to obtain a mixed solution, the mixed solution is subjected to a hydrothermal reaction and then dried to obtain the lithium aluminum hydrotalcite.
[0039] In the present invention, a lithium salt, an aluminum salt and water (referred to as first water) are mixed to obtain a mixed salt solution. In the present invention, the lithium salt is preferably LiCl; the aluminum salt is preferably AlCl3; and the first water is preferably deionized water.
[0040] In the present invention, the molar ratio of the lithium salt to the aluminum salt is preferably 3:1.
[0041] In the present invention, the total concentration of the lithium salt and the aluminum salt in the mixed salt solution is preferably 1-3M, specifically 1M, 1.5M, 2M, 2.5M or 3M.
[0042] In the present invention, NaAlO2, NaOH and water (referred to as the second water) are mixed to obtain an alkaline solution. In the present invention, the second water is preferably deionized water.
[0043] In the present invention, the molar ratio of NaAlO2 to NaOH is preferably 1:1-3, specifically 1:1, 1:2 or 1:3.
[0044] In the present invention, the total concentration of NaAlO2 and NaOH in the alkaline solution is preferably 1-3M, specifically 1M, 1.2M, 1.5M, 1.8M, 2M, 2.2M, 2.5M, 2.7M or 3M.
[0045] After obtaining the alkaline solution and the mixed salt solution, the present invention drips the alkaline solution into the mixed salt solution to obtain a mixed solution. In the present invention, the dripping is preferably performed in a protective atmosphere; the protective atmosphere is preferably an inert gas; and the inert gas is preferably argon.
[0046] In the present invention, the dropping is preferably carried out under stirring conditions; the stirring is preferably magnetic stirring; the stirring speed is preferably 300-400 rpm, specifically 300 rpm, 320 rpm, 340 rpm, 360 rpm, 380 rpm or 400 rpm.
[0047] In the present invention, the dropping temperature is preferably room temperature.
[0048] In the present invention, the dripping is preferably dropwise adding; the rate of the dropwise adding is preferably 40 to 60 drops / minute, specifically 40 drops / minute, 45 drops / minute, 50 drops / minute, 55 drops / minute or 60 drops / minute.
[0049] In the present invention, the dropping is preferably stopped when the pH value of the mixed solution is 12.9-13.
[0050] After obtaining the mixed solution, the present invention performs a hydrothermal reaction on the mixed solution and then dries it to obtain the lithium aluminum hydrotalcite. In the present invention, the temperature of the hydrothermal reaction is preferably 100 to 140°C, specifically 100°C, 110°C, 120°C, 130°C or 140°C, and the insulation reaction time is preferably 8 to 16 hours, specifically 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours.
[0051] In the present invention, after the hydrothermal reaction, the obtained product is preferably cooled and centrifuged in sequence; the final temperature of the cooling is preferably room temperature; the centrifugation is preferably stopped when the system is neutral; after the centrifugation, the obtained centrifugation product is preferably collected.
[0052] In the present invention, the drying preferably includes first drying and second drying; the temperature of the first drying is preferably 60°C, the vacuum degree is preferably -50 to -100 kPa, specifically -50 kPa, -60 kPa, -70 kPa, -80 kPa, -90 kPa or -100 kPa, and the heat preservation and drying time is preferably 12 hours.
[0053] In the present invention, the second drying temperature is preferably 150-175°C, specifically 150°C, 155°C, 160°C, 165°C, 170°C or 175°C, and the heat preservation and drying time is preferably 4-6h, specifically 5h.
[0054] The present invention also provides a lithium aluminum hydrotalcite obtained by the preparation method described in the above scheme, wherein the interlayer spacing is The interlayer anion is aluminate.
[0055] In the present invention, the size of the lithium aluminum hydrotalcite is preferably 300-800 nm, specifically 300 nm, 400 nm, 500 nm, 600 nm, 700 nm or 800 nm.
[0056] The present invention also provides a modified diaphragm, comprising a diaphragm substrate and lithium aluminum hydrotalcite covering both sides of the diaphragm substrate; the lithium aluminum hydrotalcite is the lithium aluminum hydrotalcite described in the above scheme.
[0057] In the present invention, the diaphragm substrate preferably includes a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene-polyethylene composite diaphragm or a glass fiber diaphragm; the thickness of the diaphragm substrate is preferably 20 to 30 μm, specifically 20 μm, 25 μm, or 30 μm.
[0058] In the present invention, the thickness ratio of the diaphragm substrate and the single-sided lithium aluminum hydrotalcite is preferably 3 to 6:1, specifically 4:1 or 5:1.
[0059] In the present invention, the thickness of the modified separator is preferably 30-40 μm, specifically 30 μm, 35 μm or 40 μm.
[0060] The present invention also provides a method for preparing the modified diaphragm described in the above scheme, comprising the following steps:
[0061] The lithium aluminum hydrotalcite and the binder are mixed to obtain a slurry, and the slurry is coated on both sides of the diaphragm substrate and then dried to obtain the modified diaphragm.
[0062] In the present invention, lithium aluminum hydrotalcite and a binder are mixed to obtain a slurry. In the present invention, the binder preferably includes one or both of sodium carboxymethyl cellulose and polyvinylidene fluoride.
[0063] In the present invention, the mass ratio of the lithium aluminum hydrotalcite to the binder is preferably 9:1.
[0064] After obtaining the slurry, the present invention applies the slurry to both sides of the membrane substrate and then dries it to obtain the modified membrane. In the present invention, the coating is preferably: applying the slurry to one side of the membrane substrate and then drying it, and then applying the slurry to the other side of the membrane substrate.
[0065] In the present invention, the drying temperature is preferably 50-60°C, specifically 55°C, the vacuum degree is preferably -50--100kPa, specifically -50kPa, -60kPa, -70kPa, -80kPa, -90kPa, -100kPa, and the drying time is preferably 10-12h, specifically 11h.
[0066] In the present invention, the drying temperature is preferably 50-80° C., specifically 60° C., and the heat preservation and drying time is preferably 8-14 h, specifically 12 h.
[0067] The present invention also provides a lithium battery, comprising a diaphragm and an in-situ prepared solid electrolyte; the diaphragm is the modified diaphragm described in the above scheme or the modified diaphragm obtained by the preparation method described in the above scheme; the chemical composition of the in-situ prepared solid electrolyte includes ethoxypentafluorocyclotriphosphazene.
[0068] The present invention also provides a method for preparing the lithium battery described in the above scheme, comprising the following steps:
[0069] An in-situ polymerization precursor solution is dripped on both sides of the diaphragm, and a polymerization reaction is carried out after assembly using a liquid battery assembly method to obtain the lithium battery; the diaphragm is the modified diaphragm described in the above scheme or the modified diaphragm obtained by the preparation method described in the above scheme.
[0070] In the present invention, the total amount of the in-situ polymerization precursor solution added dropwise is preferably 100 to 140 μL, and specifically may be 120 μL.
[0071] In the present invention, the chemical components of the in-situ polymerization precursor solution preferably include polymerization monomers, lithium salts, ethoxy pentafluorocyclotriphosphazene (PFPN) and initiators.
[0072] In the present invention, the polymerizable monomer is preferably 1,3-dioxolane.
[0073] In the present invention, the lithium salt preferably includes one or both of lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) and lithium bis(trifluoromethane)sulfonyl imide (LiFSI); the lithium salt concentration in the in-situ polymerization precursor solution is preferably 1-2M, specifically 1.5M or 1.8M.
[0074] In the present invention, the initiator preferably includes one of aluminum trifluoromethanesulfonate (Al(OTf)3), lithium hexafluorophosphate (LiPF6) and double salt lithium difluoro(oxalate)borate (LiDFOB); the concentration of the initiator is preferably 3 to 5 mM, specifically 4 mM.
[0075] In the present invention, the mass ratio of the ethoxy pentafluorocyclotriphosphazene to the polymerization monomer is preferably 3 to 10:100, specifically 3:100, 5:100, 7:100, 8:100 or 10:100.
[0076] In the present invention, the method for preparing the in-situ polymerization precursor solution is preferably: premixing the polymerization monomer, lithium salt and ethoxypentafluorocyclotriphosphazene to obtain a premixed solution, and then mixing the premixed solution with an initiator.
[0077] In the present invention, the premixing is preferably stirring mixing; the stirring mixing is preferably magnetic stirring mixing; the rotation speed of the stirring mixing is preferably 500-600 rpm, specifically 550 rpm, and the mixing time is preferably 10-12 h, specifically 11 h; the mixing is preferably stirring mixing; the stirring mixing time is preferably 10-20 min, specifically 15 min.
[0078] In the present invention, the polymerization reaction temperature is preferably 25-30° C., specifically 27° C., and the insulation reaction time is preferably 10-12 h, specifically 11 h.
[0079] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0080] Example 1
[0081] (1) Preparation of lithium aluminum hydrotalcite
[0082] Weigh LiCl and AlCl3 in a molar ratio of 3:1 and dissolve them in deionized water to obtain a mixed salt solution (the total concentration of the mixed salt is 1M); weigh NaAlO2 and NaOH and dissolve them in deionized water, the molar ratio of NaAlO2 and NaOH is 1:1, and obtain an alkaline solution (the total concentration of NaAlO2 and NaOH is 1M); under argon protection, room temperature, and magnetic stirring conditions, add the alkaline solution dropwise to the mixed salt solution to obtain a mixed solution, and stop until the pH value of the mixed solution is 13. The mixed solution is hydrothermally heated at 140°C for 16 hours, and after cooling to room temperature, the precipitate is collected by centrifugation and centrifuged to neutrality; the precipitate is vacuum dried for 12 hours and dried at 170°C for 4 hours to obtain lithium aluminum hydrotalcite, recorded as LiAl-LDH.
[0083] (2) Preparation of modified diaphragm
[0084] The lithium aluminum hydrotalcite and the binder were slurried in a mass ratio of 9:1, the obtained slurry was coated on one side of the diaphragm substrate, vacuum dried at 60° C. for 12 h, then coated on the other side, dried at 60° C. for 12 h, and cut into 16 mm discs to obtain a modified diaphragm.
[0085] (3) Preparation of in situ polymerization precursor solution
[0086] The DOL solution (concentration of 1 M) was transferred, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was weighed and added to the DOL solution until the concentration of LiTFSI was 1 M, then 5 wt % of PFPN (mass ratio to DOL) was transferred, and magnetic stirring was performed for 12 h. 5 mM aluminum trifluoromethanesulfonate (AL(OTf)3) was added to the resulting solution to obtain an in situ polymerization precursor solution.
[0087] (4) Preparation of lithium batteries
[0088] The battery assembly method of this embodiment is the same as the liquid battery assembly method, except that the diaphragm (PE / PP / glass fiber) in the liquid battery is replaced with the modified diaphragm in step (2), and in the step of dripping the electrolyte, 55 μL of the in-situ polymerization precursor solution is dripped on both sides of the diaphragm. After the assembly is completed, the battery is placed at 27°C for polymerization reaction for 11 hours to obtain a lithium battery.
[0089] Example 2
[0090] The preparation method of this embodiment is the same as that of embodiment 1, except that the mass ratio of PFPN to DOL is adjusted to 3 wt %.
[0091] Example 3
[0092] The preparation method of this embodiment is the same as that of embodiment 1, except that the mass ratio of PFPN to DOL is adjusted to 10 wt %.
[0093] Example 4
[0094] The preparation method of this embodiment is the same as that of embodiment 1, except that the temperature of the hydrothermal reaction is 110° C. and the time is 16 h.
[0095] Example 5
[0096] The preparation method of this embodiment is the same as that of embodiment 1, except that the temperature of the hydrothermal reaction is 110° C. and the time is 8 h.
[0097] Comparative Example 1
[0098] The preparation method of this comparative example is the same as that of Example 1, except that no PFPN is added.
[0099] Comparative Example 2
[0100] The preparation method of this comparative example is the same as that of Example 1, except that no lithium aluminum hydrotalcite is added.
[0101] Test Example 1
[0102] The lithium aluminum hydrotalcite prepared in Example 1 was subjected to XRD spectrum analysis, infrared analysis and scanning electron microscopy analysis, and the lithium aluminum hydrotalcite prepared in Examples 4 and 5 was subjected to scanning electron microscopy analysis. The structure is as follows: Figures 1 to 3 As shown. Figures 1 to 3 It can be seen that lithium aluminum hydrotalcite has a layered structure; the difference in peak position indicates that the interlayer spacing is larger than that of conventional lithium aluminum hydrotalcite, and the larger interlayer spacing helps to improve the ion conductivity of lithium aluminum hydrotalcite; the surface of lithium aluminum hydrotalcite is smooth and flaky, and the material size is at the nanoscale; its interlayer anion is aluminate.
[0103] Test Example 2
[0104] The cycle performance of the lithium battery prepared in Example 1 and Comparative Example 1 was compared. Figure 4 As shown. Figure 4 It can be seen that the lithium battery prepared by the present invention has a more excellent cycle performance, and its coulombic efficiency reaches 99.94%.
[0105] Test Example 3
[0106] The multi-rate performance of the lithium battery prepared in Example 1 and Comparative Example 1 was compared. Figure 5 As shown. Figure 5 It can be seen that the lithium battery prepared by the present invention has better rate performance.
[0107] Test Example 4
[0108] The lithium battery prepared in Example 1 was subjected to LSV test, and the results were as follows: Figure 6 As shown. Figure 6 It can be seen that the lithium battery prepared by the present invention has a wider electrochemical window.
[0109] Test Example 5
[0110] The lithium batteries prepared in Example 1 and Comparative Example 1 were subjected to EIS tests. The results are as follows: Figure 7 As shown. Figure 7 It can be seen that the lithium battery prepared by the present invention has higher ion conductivity.
[0111] Test Example 6
[0112] The long cycle performance test of the lithium batteries prepared in Example 1 and Comparative Example 2 was carried out. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that the lithium battery prepared by the present invention has better cycle performance.
[0113] Test Example 7
[0114] The lithium batteries prepared in Example 1 and Comparative Example 2 were tested for multiple rate performance. The results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that the lithium battery prepared by the present invention has a more excellent rate performance; the initial specific capacity of the battery after the diaphragm is modified is 147 mAh / g, while the initial specific capacity of the unmodified diaphragm is only 137 mAh / g, and the ionic conductivity is increased to about 1.4 mS / cm after the diaphragm is modified.
[0115] Test Example 8
[0116] The lithium batteries prepared in Example 1 and Comparative Example 2 were subjected to EIS tests. The results are as follows: Fig.10 As shown. Fig.10 It can be seen that the lithium battery prepared by the present invention has high ionic conductivity and excellent coulombic efficiency.
[0117] Test Example 9
[0118] The ionic conductivity of the lithium batteries prepared in Example 1 and Comparative Example 1 was tested, and the results are shown in Table 1.
[0119] Table 1 Ionic conductivity of lithium batteries of Example 1 and Comparative Example 1
[0120] LDH@PP +5% PFPN Thickness(μm) 38 38 R(Ω) 1.432 1.539 <![CDATA[Contact area (cm 2 )]]> 1.91 1.91 Ionic conductivity (mS / cm) 1.39 1.29
[0121] It can be seen from Table 1 that the lithium battery prepared by adding PFPN in the present invention has better ionic conductivity and electrochemical performance.
[0122] Test Example 10
[0123] The ionic conductivity of the lithium batteries prepared in Example 1 and Comparative Example 2 was tested, and the results are shown in Table 2.
[0124] Table 2 Ionic conductivity of lithium batteries of Example 1 and Comparative Example 2
[0125] PP LDH@PP Thickness(μm) 31 38 R(Ω) 1.773 1.432 <![CDATA[Contact area (cm 2 )]]> 1.91 1.91 Ionic conductivity (mS / cm) 0.91 1.39
[0126] It can be seen from Table 2 that the lithium battery prepared by the lithium aluminum hydrotalcite modified diaphragm in the present invention has more excellent ionic conductivity and electrochemical performance.
[0127] It can be seen from the above examples that the lithium aluminum hydrotalcite provided by the present invention is easy to control in size, stable at room temperature, has high ion conductivity, and the prepared lithium battery has excellent electrochemical performance.
[0128] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing lithium aluminum hydrotalcite, characterized in that: The following steps are involved: A lithium salt, an aluminum salt and water are mixed to obtain a mixed salt solution, NaAlO2, NaOH and water are mixed to obtain an alkaline solution, the alkaline solution is added dropwise to the mixed salt solution to obtain a mixed solution, the mixed solution is subjected to a hydrothermal reaction and then dried to obtain the lithium aluminum hydrotalcite; the temperature of the hydrothermal reaction is 100 to 140°C.
2. The preparation method according to claim 1, characterized in that: The dropping is carried out in a protective atmosphere, the dropping is carried out under stirring conditions, the dropping temperature is room temperature, the dropping is drop-by-drop, and the dropping is stopped when the pH value of the mixed solution is 12.9-13.
3. The preparation method according to claim 1, characterized in that: The heat preservation reaction time of the hydrothermal reaction is 8 to 16 hours.
4. The lithium aluminum hydrotalcite obtained by the preparation method according to any one of claims 1 to 3 has an interlayer spacing of The interlayer anion is aluminate.
5. The lithium aluminum hydrotalcite according to claim 4, characterized in that The size of the lithium aluminum hydrotalcite is 300-800 nm.
6. A modified diaphragm, characterized in that: It comprises a diaphragm substrate and lithium aluminum hydrotalcite covering the surfaces of both sides of the diaphragm substrate; the lithium aluminum hydrotalcite is the lithium aluminum hydrotalcite according to any one of claims 4 to 5.
7. The modified diaphragm according to claim 6, characterized in that: The thickness ratio of the diaphragm substrate and the single-sided lithium aluminum hydrotalcite is 3 to 6:
1.
8. The method for preparing the modified diaphragm according to any one of claims 6 to 7, characterized in that: The following steps are involved: The lithium aluminum hydrotalcite and the binder are mixed to obtain a slurry, and the slurry is coated on both sides of the diaphragm substrate and then dried to obtain the modified diaphragm.
9. A lithium battery, characterized in that: It comprises a diaphragm and an in-situ prepared solid electrolyte; the diaphragm is the modified diaphragm according to any one of claims 6 to 7 or the modified diaphragm obtained by the preparation method according to claim 8; the chemical composition of the in-situ prepared solid electrolyte comprises ethoxypentafluorocyclotriphosphazene.
10. The method for preparing a lithium battery according to claim 9, characterized in that: The following steps are involved: An in-situ polymerization precursor solution is dripped on both sides of the diaphragm, and a polymerization reaction is carried out after assembly using a liquid battery assembly method to obtain the lithium battery; the diaphragm is the modified diaphragm described in any one of claims 6 to 7 or the modified diaphragm obtained by the preparation method of claim 8; the chemical components of the in-situ polymerization precursor solution include polymerization monomers, lithium salts, ethoxypentafluorocyclotriphosphazene, initiators and solvents.